Computational Algorithms for Sustainability Assessment - Marvuglia, Antonino; Murgante, Beniamino; Benetto, Enrico (Journal of Environmental Accounting and Management, 2026)
Due to the increasingly complex environmental system problems science and society have to deal with, an integrated methodological framework for sustainability assessment is by nature rooted in an interdisciplinary approach. In particular, practical implementation and monitoring, to manage the transition from business-as-usual to sustainable development paths for the concerned stakeholders requires improving the knowledge (and the capacity to communicate it) on linkages between the key types of resources, the resources and the environment and the resources and the economy. The underlying challenges are inherently integrated and shall be pursued in combination. That is why an integrated approach is essential. This special issue aims at presenting research show cases which bridge together different research communities, especially Computational Geography, Environmental Informatics and Life Cycle Assessment (LCA), which have so far come to common grounds only in a few cases.